2000
DOI: 10.4049/jimmunol.165.11.6606
|View full text |Cite
|
Sign up to set email alerts
|

CTLA-4 Gene Polymorphism at Position 49 in Exon 1 Reduces the Inhibitory Function of CTLA-4 and Contributes to the Pathogenesis of Graves’ Disease

Abstract: Activation of T cells requires at least two signals transduced by the Ag-specific TCR and a costimulatory ligand such as CD28. CTLA-4, expressed on activated T cells, binds to B7 present on APCs and functions as a negative regulator of T cell activation. Our laboratory previously reported the association of Graves’ disease (GD) with a specific CTLA-4 gene polymorphism. In theory, reduced expression or function of CTLA-4 might augment autoimmunity. In the present study, we categorized autoimmune thyroid disease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
338
3
11

Year Published

2003
2003
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 467 publications
(372 citation statements)
references
References 48 publications
20
338
3
11
Order By: Relevance
“…There was no difference in the expression of CTLA-4 and in the inhibitory function of CTLA-4 when T cells were transfected with CTLA-4 cDNA carrying the G or the A allele, suggesting that the A and G alleles of the CTLA-4 A/G 49 SNP did not directly influence its function. 47 Thus, our results and previous results showing decreased function and/or expression of CTLA-4 in individuals carrying the G allele [44][45][46] must reflect the effects of another CTLA-4 polymorphism that is in linkage disequilibrium with the A/G 49 SNP. Therefore, the A/G 49 SNP can be used as a surrogate marker until the causative polymorphism is identified.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…There was no difference in the expression of CTLA-4 and in the inhibitory function of CTLA-4 when T cells were transfected with CTLA-4 cDNA carrying the G or the A allele, suggesting that the A and G alleles of the CTLA-4 A/G 49 SNP did not directly influence its function. 47 Thus, our results and previous results showing decreased function and/or expression of CTLA-4 in individuals carrying the G allele [44][45][46] must reflect the effects of another CTLA-4 polymorphism that is in linkage disequilibrium with the A/G 49 SNP. Therefore, the A/G 49 SNP can be used as a surrogate marker until the causative polymorphism is identified.…”
Section: Discussionsupporting
confidence: 73%
“…Similarly, other investigators have examined the effects of the A and G alleles of the CTLA-4 A/G 49 SNP on the inhibitory function of CTLA-4. [44][45][46] The GG genotype was found to be associated with reduced inhibitory function of CTLA-4 on T-cell proliferation after stimulation with an allogeneic cell line, and with decreased CTLA-4 surface expression. [44][45][46] This could imply that the A and G alleles of the CTLA-4 leader sequence influenced its function and/or expression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequently, the three known polymorphisms of the CTLA-4 gene were investigated for linkage and/or association in a large number of human autoimmune diseases. Of interest, some polymorphisms of the gene, such as those of exon 1 which alter CTLA-4 transcription, increase susceptibility to type 1 diabetes (T1D) and other autoimmune diseases [16][17][18][19].…”
Section: Autoimmunity and Ctla-4 Geneticsmentioning
confidence: 99%
“…1,2 The search for genes that predispose such disease is complicated by their polygenic nature. Until recently, only the major histocompatibility complex (MHC) 3,4 and cytotoxic T-lymphocyte antigen-4 (CTLA-4) [5][6][7] have been consistently found associated with GD. With regard to the adhesion molecule, Kretowski A et al 8 had reported that intercellular adhesion molecule 1 (ICAM-1) gene polymorphisms were associated with GD.…”
Section: Introductionmentioning
confidence: 99%